Non-Iranian Origin of the Eastern-Slavonic God Xŭrsŭ/XorsNeiranskoe proishoždenie vostočnoslavjanskogo boga Hrsa/Horsa - Borissoff, Constantine L. (Studia mythologica Slavica, 2014)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The paper examines the traditional explanation of the Eastern-Slavonic deity Xors as an Iranian loan from the Persian xwaršēδ/xoršid ‘sun’ and advances an alternative etymology via the Indo-Aryan root hṛṣ-, Indo-European *g̑hers- and its cognates in other Indo-European languages. Based on the linguistic and mythological comparative analysis Xors is interpreted not as an abstract ‘solar god’ but as a ‘sun fertility hero’ viewed as the development of the ancient archetype of the ‘dying and resurrecting god’ comparable in role to Dionysus. The paper closes with a brief outline of some new venues for research following out of the proposed reinterpretation of Xors.